Factors Influencing Citizen Trust towards Armed Police Force Nepal: A Study on Border Crossing Points - Upreti, Yukesh (Journal of APF Command and Staff College, 2025)
Citizen trust of border governing agencies is considered as a crucial task for good border governance. This research paper examines the relationship between the determinant factors of citizen trust towards Armed Police Force (APF), Nepal at Border crossing points. The research follows quantitative approach with correlation design. The primary sources of data are taken from the respondents at two major Border crossing points. Secondary sources of data are taken from online sources, journal, publication, reports and recorded data from APF Border Security Department. The finding shows clear relationship between the determinant factors of citizen trust toward the APF, Nepal. The correlation analysis shows highly significant of citizen trust with determinant factors which are integrity, competency, benevolence, honesty and service delivery. The regression model is highly significant and the model fits the data. The acceptance of the alternative hypotheses for both categories of variables indicates that determinant factors play a significant role in shaping public perceptions and trust towards APF, Nepal at Border crossing point and help in building public confidents.